Iodine monoxide in the Antarctic snowpack - Frieß, Udo; Deutschmann, Tim; Gilfedder, Benjamin Silas; Weller, Rolf; Platt, Ulrich (Atmospheric chemistry and physics, 2010)
Recent ground-based and space borne observations suggest the presence of significant amounts of iodine monoxide in the boundary layer of Antarctica, which are expected to have an impact on the ozone budget and might contribute to the formation of new airborne particles. So far, the source of these iodine radicals has been unknown. This paper presents long-term measurements of iodine monoxide at the German Antarctic research station Neumayer, which indicate that high IO concentrations in the order of 50 ppb are present in the snow interstitial air. The measurements have been performed using multi-axis differential optical absorption spectroscopy (MAX-DOAS). Using a coupled atmosphere – snowpack radiative transfer model, the comparison of the signals observed from scattered skylight and from light reflected by the snowpack yields several ppb of iodine monoxide in the upper layers of the sunlit snowpack throughout the year. Snow pit samples from Neumayer Station contain up to 700 ng/l of total iodine, representing a sufficient reservoir for these extraordinarily high IO concentrations.
Gesehen am 11.07.2023